IT Infrastructure Capability, Competitive Advantage and Software Development Project Success in Public Sector - Rozaida, M. D.; Yuserrie, Zainuddin; Mahanum, Daim (International Institute of Social and Economic Sciences, Czech Republic, 2014)
The paper focuses on applying Resource-based view (RBV) of organization to achieve competitive advantage and enhancing the success of software development project. Software development projects are known for being completed far over budget and behind schedule. The high investment of information technology (IT) infrastructure capability required money, time and effort must be able to deliver value to organization. In such organization, the software development project must be managed and controlled by IT manager. The IT manager of the software development project has to ensure that the project finishes on schedule and within budget. Therefore, software development need to be more strategic of planning and design where recent software development approaches emphasis more upon technical skills of coding and debugging and ignore the strategic importance of planning and design. Specifically, we based our research on the conceptual framework of RBV to investigate the relationships among IT infrastructure capability and software development project success, IT infrastructure capability and competitive advantage, competitive advantage and software development project success and that the competitive advantage mediates the relationship between IT infrastructure capability and software development project success. The findings will indicate on how organization should focus with their IT infrastructure capability through competitive advantage, which will result in the success of software development project in Malaysian public sector.